Mengenal Reog dan Warok Dalam Kebudayaan Masyarakat Ponorogo - Pramudita, Nicolas Gerardus Dimas (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2014)
Ponorogo is one of the districts in Indonesia which has a very specific inheritance, namely the socalled Reog and Warok arts. Both are parts of performance art. Reog is a form of colosal dance, which came up to retell the legend of Ponorogo. Its performance is not just intended fo entertaining me society but also a sebagai sarana sinidiran. It depends on which version is taken out. On the other hand, Warok is a cultural fenomena exists within the Ponorogo society. From time to time the Warok tradition has endured an altered meaning depends on the influence of time and religious doctrine.